Comparison of 2D and 3D prediction models for environmental vibration induced by underground railway with two types of tracks. (July 2015) - Xu, Qingyuan; Xiao, Zucai; Liu, Tao; Lou, Ping; Song, Xuming
Abstract: In this paper, two-dimensional (2D) and new types of three-dimensional (3D) prediction models of environmental vibrations induced by underground railways with a direct fixation track and steel spring floating slab track are developed and verified. The ground surface responses calculated by the 2D prediction models with various equivalent forces are compared with those calculated by the 3D prediction models. The numerical results show that (a) the ratio of the computational time by the 2D prediction models to that by the 3D prediction models is less than 1/600; thus, the 2D prediction models can quickly provide useful results; (b) the equivalent forces in the 2D prediction models are key and are recommended for use as the equivalent wheel–rail force and equivalent steel spring force averaged over a vehicle length for an underground direct fixation track and steel spring floating slab track, respectively; and (c) the accuracy of the 3D prediction models is greater than that of the 2D prediction models; therefore, the 3D prediction models are required for absolute prediction due to their higher accuracy and applicability in a wider range of complex practical problems.